1998
DOI: 10.1159/000045188
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Hypertrophy as a Prognostic Marker in Childhood IgA Nephropathy

Abstract: A clinicopathological and morphometric analysis of glomerular hypertrophy (GH) was conducted using biopsies obtained from 52 selected pediatric patients with IgA nephropathy (IgAN). Of the 52 patients, consisting of 12 with chronic renal failure (CRF) and 40 without CRF, various clinical and morphometric parameters were compared to 10 controls with benign hematuria. The mean glomerular tuft size, mesangial area, and interstitial area all significantly increased in patients with poor prognosis when compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…We used the point-counting method [11]to evaluate amyloid deposition in the tubular basement membrane and/or interstitium. Under high magnification (×400) using an 81-point (100-square) eyepiece micrometer, at least 10 consecutive nonoverlapping cortical fields were analyzed from each biopsy section.…”
Section: Methodsmentioning
confidence: 99%
“…We used the point-counting method [11]to evaluate amyloid deposition in the tubular basement membrane and/or interstitium. Under high magnification (×400) using an 81-point (100-square) eyepiece micrometer, at least 10 consecutive nonoverlapping cortical fields were analyzed from each biopsy section.…”
Section: Methodsmentioning
confidence: 99%
“…For the evaluation of (5) glomerular hypertrophy (glomerular tuft area in glomerular cross-section), (6) activated mesangial cells (␣-actinϩ area in glomerular crosssection), and (7) mesangial matrix accumulation (periodic acid silver methenamineϩ area in glomerular cross-section), 40 cross-sections of glomeruli were assessed by Luzex IIIU digital image processor analyzer (Nireco, Tokyo, Japan), and expressed in m 2 , as described previously (Masseroli et al, 1998;Nishimoto et al, 1997;Tóth and Takebayashi, 1998). These results were expressed as the mean Ϯ SD or SEM, and statistical analysis was performed using the unpaired Student's t test.…”
Section: Quantification Of Histological Findingsmentioning
confidence: 99%
“…Apart from obesity and child renal disease, glomerular hypertrophy is also often seen in cases of hypertension, FSGS and progressive IgAN. Microscopic examination of renal biopsies of such patients often shows cystic dilatation of the glomerular loop with loop elongation [14,[20][21][22]. It is thought that these changes result in damage to glomerular epithelial cells and subsequently lead to their adhesion to Bowman's capsule and development of segmental sclerosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that these changes result in damage to glomerular epithelial cells and subsequently lead to their adhesion to Bowman's capsule and development of segmental sclerosis [23]. We have reported that the appearance of cystic capillary expansion may be important indicators of renal prognosis in VUR [14] and IgAN [21].…”
Section: Discussionmentioning
confidence: 99%